EFFECT OF MEDIA CULTURES AND BENZYLADENINE (BA) CONCENTRATIONS IN MICROPROPAGATION OF THREE TYPES OF CHERRY ROOTSTOCK (ESTABLISHMENT AND MULTIPLICATION) - & et al., Bani (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This expereament was carried out in plant tissue culture laboratory of the Horticulture Department, Faculty of Agriculture, University of Duhok, Iraq, during 2014, using two types of explants (Shoot tips and nod segments) in the establishment stage. The highest percentage of shoot /explant (100%) was obtained from Stockton Morello rootstock on both media, while 96.88% was recorded with WPM (Woody plant medium) from nodal segment in F12/1 Mazzard and (87.5%) was observed from shoot tip in Mohaleb. While the highest shoot number with three rootstocks (24.50, 24.38 and 22.25 shoot /explant) with Stockton Morello, F12/1 Mazzard and Mahaleb respectively, were recorded from nodal segment with WPM. While the lowest number of shoots (19.63 shoots /explant) was formed when the shoot tips were cultured on MS medium. At the multiplication stage, the maximum number of shoot per explant (9.50 and 9.17 shoots /explant) in Stockton Morello rootstock was recorded with WPM and MS medium provided with 3mg l-1 BA. The interaction of Stockton Morello with WPM and MS medium having 1.5 mg l-1 BA produced an average of shoot length (3.58 and 3.52 cm) and the increased of shoot length was significantly compared with all treatment without the treatment in combination of Stockton Morello rootstock in WPM medium supplemented with 3 mg l-1 BA. Also the highest length of shoot per explant with three rootstocks 3.58 and 2.98 cm in Stockton Morello and F12/1 Maazard were recorded in WPM having 1.5mg l-1 BA and in Mahaleb rootstock (2.92 cm) was recorded on MS medium containing 1.5mg l-1 BA.